Enhanced Collaborative Teaching Method on the Performance of Students in Essay Writing Task - Timothy Kolade Akinwamide (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
The art of Writing as a basic language skill in Language Education, is a generative skill that requires a lot of brainstorming in order for Second Language students to meet up with the acceptable communicative competence expected. Where and when individuals collaborate on a given work, the resultant effect is normally encouraging hence this research work examined the effects of collaborative teaching method on the writing task of students. The paperemployed the collaborative pedagogy on enhancing students’ academic performance in essay writing at the Senior Secondary School level. The study adopted a quasi-experimental design approach. The sample consisted of 50 Senior Secondary School final year students. The data generated were subjected to statistical analysis and the results of the analysis showed that there was no significant difference between the pre-test scores of both the control and experimental group which established the homogenuityof both control and experimental groups before the application of treatment on the experimental group . There was no significant difference in the pre-test and post test scores of the students in control group. However the collaborative method which was the treatment had significant effect on students overall performance in essay writing. Therefore,it is recommended that English language teachers could employ this method for improved performance among students. Also, teachers should encourage teamwork among students for the exchange of novel ideas. To this effect, educational institutions could organise and train teachers on how to secure better performance through collaborative pedagogical inputs.